Implementation of the Policy for Using Village Funds in Pabean Udik Village, Indramayu District, Indramayu Regency - Ismanudin; Ilham Stiawan (Public Policy: Jurnal Ilmu Sosial dan Kebijakan, 2025)
The problem with this research is that the implementation of the policy of using village funds in Pabean Udik Village, Indramayu District, Indramayu Regency still seems less than optimal. The research method used is a descriptive method with a qualitative approach. The analysis unit in this research includes all implementing elements and village communities in the use of Village Funds in Pabean Udik Village. Data collection techniques are library studies and field studies using direct interview techniques, field observations, and documentation techniques. Data analysis using qualitative descriptive data analysis techniques. The results of this research show that the implementation of the policy for using village funds in Pabean Udik Village is quite good, but there are still several obstacles in implementing this policy. However, there have been efforts made by the village government to overcome every problem that arises and develops at the village community level in the use of village funds in accordance with the village's authority.